A Qualitative Research on the Changing/Transforming Professions of Gypsies Living in Elazig - Firat, Muhammet; Acikgoz, Resat (Istanbul Univ, Methodology & Sociology Research Center, 2020)
In this study, Gypsies are discussed in the context of changing/transforming professions and the results of this professional transformation for Gypsies and their professional processes in urban environments are examined. The changing/transforming labour relations in industrial capitalist societies with technological developments not only exclude Gypsies in terms of ethnicity, but also compel them to work in precarious/irregular/risky jobs, which are often not preferred professionally. The in-depth interview technique, one of the qualitative research methods, was used in the study. The study was conducted between November-December 2018 and January 2019 with 20 young-adult interviewers in order to probe how changing working conditions affect Gypsies in such processes as economy, culture, identity, social status and way of life in 4 neighbourhoods in Elazig city centre where Gypsies are densely populated. The results show that Gypsies have started to experience more challenging processes both culturally and economically as a result of being unable to keep up with the new developments with their changing/transforming working life. The decrease/disappearance of the professions reflecting their Gypsy identity (metalworking, siever, etc.) leads them to work in marginal temporary and informal sectors, which are often disliked, or which are not willing to be done by non-Gypsies. Furthermore, the disappearance of their profession, which affirms their social status and identity, makes the pejorative connotation of the word Gypsy more visible, causing marginal jobs such as begging, porters, etc. to be identified with Gypsies and such jobs to become more of a necessity than a preference for Gypsies. As a result, Gypsies, because of their traditional profession disappearance try to make a living and hold on to life by doing jobs which are not their own choices but which urban working conditions impose on them.
Keywords: Gypsies; Ethnicity; Occupation; Informal Employment; Exclusion